Characterization of the consumption of dairy foods in users of markets and supermarkets in Guayaquil, Ecuador - Vargas, Pablo (2024)
Ecuador is a country that presents a great diversity of cultures and traditions, which is reflected in its gastronomy. However, the pandemic changed certain approaches to food consumption, especially locating those that included medicinal properties or specifically with antioxidant characteristics, rich in Vitamin C; and other particularities that provide resistance against the SARS-COV-2 virus, known as coronavirus. Dairy products consumption underwent changes, with some reducing their daily intake, while others increasing it. Thus, this study is proposed to define the characteristics of dairy product consumption in the city of Guayaquil, in the year 2021; based on the survey conducted to a sample of 820 people, users of markets and supermarkets in the city of Buenos Aires; matrix constructed from the DRECA study: Diet and Risk of Cardiovascular Diseases in Andalusia, 1999; and adjusted to the typologies of the Guayaquil environment. The results show that, of 15 regularly consumed dairy products, 3 had a higher weekly intake, including whole milk and yogurt as well as cream cheese. In the case of yogurt and whole milk, they have a greater incidence in the population with consumption between 1 time a week and 5 - 6 times a week in portions of one cup or 200 cc; while in the case of cream cheese there is a higher consumption, 2 – 4 times a week in segments of 25 g. These three products represent the most consumed, considered weekly consumption, included in the diet, given their organoleptic and access characteristics.